2022
DOI: 10.1097/pts.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Uniformity of Clinical Judgment: A Vignette Approach to Understanding Healthcare Professionals’ Suicide Risk Assessment Practices

Abstract: Objectives: Suicide risk assessment often requires health professionals to consider a complex interplay of multiple factors, with a significant reliance on judgment, which can be influenced by factors such as education and experience. Our study aimed at assessing the uniformity of decision making around suicide risk within healthcare professionals. Methods:We used a factorial survey approach to gather information on healthcare professionals' demographics, clinical experience, and their decision on 3 vignettes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…These differences may also be due to the use of the MIRECC model of suicide risk utilized in the current study, which notes protective factors and preparatory behaviours as key features that distinguish between high and intermediate acute risk.Despite the use of a specific model of risk stratification, the current study identified variability in the risk and disposition decisions of participants, consistent with outcomes in previous research(Pease et al 2017;Sequeira et al 2022). For example,Pease et al (2017) noted variability in assessments of imminent risk related to the presence of suicidal ideation and preparatory behaviours in the vignettes, whileSequeira et al (2022) identified variability in disposition determination related to provider experience. Due to sample size, impacts of clinician experience on variability could not be empirically tested in the current study.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…These differences may also be due to the use of the MIRECC model of suicide risk utilized in the current study, which notes protective factors and preparatory behaviours as key features that distinguish between high and intermediate acute risk.Despite the use of a specific model of risk stratification, the current study identified variability in the risk and disposition decisions of participants, consistent with outcomes in previous research(Pease et al 2017;Sequeira et al 2022). For example,Pease et al (2017) noted variability in assessments of imminent risk related to the presence of suicidal ideation and preparatory behaviours in the vignettes, whileSequeira et al (2022) identified variability in disposition determination related to provider experience. Due to sample size, impacts of clinician experience on variability could not be empirically tested in the current study.…”
supporting
confidence: 83%
“…Vignette studies examining the role of different risk factors on suicide risk assessment have found considerable variability in assessment outcomes between participants. While risk factors related to the presence of a plan and preparatory behaviours are among the most important factors for elevated risk, they also demonstrated the most variability in assessed risk levels among the vignettes (Pease et al 2017;Sequeira et al 2022). Weiland et al (2014) found that assessed risk level was the strongest predictor of disposition, and while they reported general consistency in disposition decisions, more experienced clinicians were more likely to recommend admittance in an emergency setting.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations